2009
DOI: 10.1111/j.1365-2133.2009.09568.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression levels of testis-specific genesTEX101andSPATA19in basal cell carcinoma and their correlation with clinical and pathological features

Abstract: We report five new CT antigens, of which SPATA19 and TEX101 may be possible targets for cancer immunotherapy and novel markers for early detection of BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 30 publications
(26 reference statements)
1
38
0
Order By: Relevance
“…In addition, TSGA10 expression has been demonstrated in embryonic stem cell, in actively dividing cells, in fetal differentiating tissues and also in various primary tumors, (16) therefore it could be classified as CT antigen. Previously, our studies showed expression of TEX101, SPATA19 and LEMD1 in basal cell carcinoma (17) and prostate cancer (18, 19). …”
Section: Discussionmentioning
confidence: 70%
“…In addition, TSGA10 expression has been demonstrated in embryonic stem cell, in actively dividing cells, in fetal differentiating tissues and also in various primary tumors, (16) therefore it could be classified as CT antigen. Previously, our studies showed expression of TEX101, SPATA19 and LEMD1 in basal cell carcinoma (17) and prostate cancer (18, 19). …”
Section: Discussionmentioning
confidence: 70%
“…2,3) Many genes which were crucial for spermatogenesis and male fertility are often exclusively expressed in male germ cells. Some testis-specific genes have been screened including FAM46D, 4) Adam31, 5) PDHA2, 6) TEX101 and SPATA19, 7) etc. which have been proven to play critical roles in the process of spermatogenesis and steroidogenesis.…”
mentioning
confidence: 99%
“…Expression has been detected in the multiple myeloma cell lines THIEL and RPMI8226, in the testis and in two of four primary multiple myeloma tumour samples (Sahota et al, 2006). Not found in 78 basal cell carcinoma by real-time PCR (Ghafouri-Fard et al, 2010).…”
Section: Expressionmentioning
confidence: 99%